3x+10=-44-6

Simple and best practice solution for 3x+10=-44-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+10=-44-6 equation:


Simplifying
3x + 10 = -44 + -6

Reorder the terms:
10 + 3x = -44 + -6

Combine like terms: -44 + -6 = -50
10 + 3x = -50

Solving
10 + 3x = -50

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 3x = -50 + -10

Combine like terms: 10 + -10 = 0
0 + 3x = -50 + -10
3x = -50 + -10

Combine like terms: -50 + -10 = -60
3x = -60

Divide each side by '3'.
x = -20

Simplifying
x = -20

See similar equations:

| 7f(f+1)= | | 19/x=12 | | 44-10y=10 | | (2x)+2=6 | | -x-8=-2x+0 | | 6+4x=9+x | | 13.28-2.9m=-17.54-7.5m | | 12+2g=24 | | 4r-22r=22 | | -16.85-5.2g=-13.7g+18.43+16.9g | | 7x-15=-41 | | 1+18v=19+19v | | 2(x)-5=31 | | 3-2x=2(1-x) | | 3a-(b-2a)=equation | | 9-14n=4-15n+13 | | -2u+7=-3u | | x^2+9x+20.25=-18 | | 4(l+1)=3(l+4) | | 2+8j=9+j | | 100=x(x+10) | | 2-4c=-8c-10+8c | | 8x-16y=6 | | 14=-10x+8x+2 | | 25(6-x)2-4(6-x)3= | | -3p+5=-8p | | 2.5x+5+4.5+1.5x-4.5=15 | | -8-d=10+d | | 6+77x=33x+30 | | -z=9-2z | | -2=-2x+2 | | 6-2b=-5b |

Equations solver categories